Molecular phylogeny and taxonomic review of Premnobiini Browne, 1962 (Coleoptera: Curculionidae: Scolytinae) - Cognato, Anthony I. (Frontiers in Ecology and Evolution, 2013)
The taxonomy of Premnobiini is reviewed in the context a molecular phylogeny including species of Ipini, Dryocoeotini, and Xyleborini. DNA data from COI, 16S, 28S, and CAD ( 2640 characters) were generated for 79 species and phylogenies were reconstructed using parsimony and Bayesian methods under different nucleotide sequence alignment parameters. The topologies of these phylogenies were in general agreement. Ipini was monophyletic along with all genera except Acathotomicus. Premnobiini was nested within Ipini and consisted of two clades, which associated with Premnobius and Premnophilus. These results justified taxonomic changes. Premnophilus was resurrected as a valid genus and Premnobiini was considered a sub-tribe of Ipini.